Qualitative, comparative, and collaborative research at large scale: An introduction to GENNOVATE - Badstue, Lone B.; Petesch, Patti; Feldman, Shelley; Prain, Gordon; Elias, Marlène; Kantor, Paula (2018)
What is the relationship between gender norms, agency, and agricultural innovation? How might we undertake and what can we learn from a comparative approach to this question? GENNOVATE—a comparative and collaborative research project—addresses these questions using contextually embedded qualitative analyses that also allow for comparison and extrapolation of patterns across multiple locations. This paper provides an overview of the conceptual approach and the methodological strategy that informed GENNOVATE's twin objectives and research design. The conceptual framework underlying this original research initiative is introduced and the challenges and opportunities faced when combining inductive and deductive analytic approaches are discussed. The empirical and methodological issues are explored and the broad relevance of GENNOVATE’s research approach beyond the field of agricultural development is reflected upon.